A systematic literature review on the problem-posing strategies for biology problem-posing multimedia module design - Ab. Wahid, Nor Tutiaini; Talib, Othman; Sulaiman, Tajularipin; Mohd Puad, Mohd Hazwan (Human Resource Management Academic Research Society, 2018)
Numerous research has documented the debate fuelled by scholars pertaining to problem-posing strategy in Mathematics. It has been argued that this strategy is capable of instilling student’s problem-solving skills. However, despite its popularity in Mathematics, the application on other subjects such as Biology particularly, via a media technology is still sparse. This study aims at identifying suitable strategies to be incorporated into a proposed multimedia module namely, Problem-Posing Multimedia Module (PPMM). To achieve the objective, a systematic literature review has been executed. This paper elaborates on the rigorous systematic literature review process done on the 289 selected journal articles and papers on problem-posing strategies topic. The analysis reveals that, while different field applies different strategies of problem-posing, most of them share similar themes in implementing problem-posing instructional strategies. These are communication, collaboration, creativity and critical thinking, which are part of the elements advocated in the 21st-century learning. These findings act as a heuristic device to propose a development of a problem-posing multimedia activity module.